One river, two streams: chemical and chromium isotopic features of the Neglinka River (Karelia, northwest Russia). Issue 8 (11th June 2019) - Andronikov, A. V.; Novak, M.; Borodulina, G. S.; Efremenko, N. A.; Andronikova, I. E.; Chesalina, G. L.; Levichev, M. A.; Subetto, D. A.; Sebek, O.; Zobkova, M. V.
ABSTRACT: The physico-chemical and hydrochemical characteristics of run-off of the Neglinka River Basin (northwest Russia) monitored for a year are different for the upstream and downstream sections. The river known hydrologically as the Neglinka, consists hydrochemically of two different streams: one represented by the upstream part of the basin, and the other one by the downstream. The upstream water is characterized by low mineralization (water hardness 0.08–0.43 mmol L −1 ) and low δ 53 Cr values (+0.30 to +0.42‰), whereas the lower part is characterized by high mineralization (water hardness 0.37–3.46 mmol L −1 ) and high δ 53 Cr values (+0.92 to +1.73‰). The difference in chemical composition of the upstream and downstream waters could be due to the underground discharge input. Aqueous chromium (Cr) mobilized from weathering profiles may have been reduced from soluble Cr(VI) to insoluble Cr(III) during the riverine transportation. Partial removal of Cr from the water balance resulted in a decrease in Cr concentration and an increase in δ 53 Cr values.